Factors influencing the provision of public health services by village doctors in Hubei and Jiangxi provinces, China - Yan Ding; Helen J Smith; Yang Fei; Biao Xu; Shaofa Nie; Weirong Yan; Vinod K Diwan; Rainer Sauerborn; Hengjin Dong (The World Health Organization, 2013)
PROBLEM: The Chinese central government launched the Health System Reform Plan in 2009 to strengthen disease control and health promotion and provide a package of basic public health services. Village doctors receive a modest subsidy for providing public health services associated with the package. Their beliefs about this subsidy and providing public health services could influence the quality and effectiveness of preventive health services and disease surveillance. APPROACH: To understand village doctors'perspectives on the subsidy and their experiences of delivering public health services, we performed 10 focus group discussions with village doctors, 12 in-depth interviews with directors of township health centres and 4 in-depth interviews with directors of county-level Centers for Disease Control and Prevention. LOCAL SETTING: The study was conducted in four counties in central China, two in Hubei province and two in Jiangxi province. RELEVANT CHANGES: Village doctors prioritize medical services but they do their best to manage their time to include public health services. The willingness of township health centre directors and village doctors to provide public health services has improved since the introduction of the package and a minimum subsidy, but village doctors do not find the subsidy to be sufficient remuneration for their efforts. LESSONS LEARNT: Improving the delivery of public health services by village doctors is likely to require an increase in the subsidy, improvement in the supervisory relationship between village clinics and township health centres and the creation of a government pension for village doctors.